Efficacy of bulevirtide as monotherapy for chronic hepatitis D (CHD): Week 48 results from an integrated analysis. (March 2023) - Lampertico, P.; Aleman, S.; Blank, A.; Bogomolov, P.; Chulanov, V.; Mamonova, N.; Morozov, V.; Sagalova, O.; Stepanova, T.; Suri, V.; Manuilov, D.; Ye, L.; et al.
Abstract : Introduction: Bulevirtide (BLV) is a novel first-in-class entry inhibitor for the treatment of chronic hepatitis delta virus (HDV) infection (CHD) that was conditionally approved in the EU in July 2020. Patients treated with BLV had pronounced HDV RNA and alanine transaminase (ALT) declines through 48 weeks (W) in a Phase 2 study (MYR203; NCT02888106) and 24W in a Phase 3 study (MYR301; NCT03852719). Aim: We present an integrated analysis of 48W efficacy derived from MYR203/MYR301. Method and Results: Patients with CHD (N=180) ± compensated cirrhosis were included in a pooled 48W analysis of BLV 2 (n=64) or 10 mg (n=65) given subcutaneously once daily vs no active anti-HDV treatment (n=51; control). The primary efficacy endpoint was combined response (CR; undetectable HDV RNA or decrease by ≥2 log10 IU/mL from baseline and ALT normalization); additional endpoints included viral response, ALT normalization, and log10 change in HDV RNA levels. Baseline demographics were well balanced across groups. The 48W CR rate was similar in the BLV 2 vs 10 mg groups (46.9% vs 46.2%) and higher than control (2.0%). While rates of ALT normalization at 48W were similar for those treated with BLV 2 and 10 mg (56.3% and 52.3%), the viral response rate was numerically lower in the BLV 2 than in the BLV 10 mg group (68.8% and 78.5%), with mean change from baseline in HDV RNA of −2.60 and −3.29 log10 IU/mL. All efficacy endpoint response rates were higher in the BLV groups vs the control group. Treatment benefit was consistent across subgroups treated with BLV. Conclusion: Among patients with CHD, efficacy at 48W was comparable between BLV 2 and 10 mg, and both were better than control. These results provide additional support for the use of BLV 2 mg for treatment of compensated CHD.